CONSUMER PERCEPTION OF FISH WATER IN MORNING MARKETS PANAM CITY OF PEKANBARU - Ananda, Ananda; Kusai, Kusai; Darwis, Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACKResearch on consumer perception of fish water at morning markets Panam city of Pekanbaru had been done in february to april 2018 in morning markets Panam city of Pekanbaru. The purpose of this research to know consumer perception of fish water based characteristics and consumer behaviour in identifying the attributes of fish water. The data collection had done by observation, interviews and recording then data measured using a likert scale and descriptive analysis. The attribute of the fish water in the morning market at Panam its very good. It is seen at the price, offered, The convenience of consumers, and the distance that must be taken by the consumers. Is not to far away. The quality of the fish marketed is in accordance with the wishes of the costumers. It can seen from the form of the fish that is marketed, ranging from the condition of the meat, the situation of scales and the color of the gills. Keyworsd : Perception, Consumers, Fish Water, Morning markets Panam